2015
DOI: 10.1007/s10552-015-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors/angiotensin receptor blockers therapy and colorectal cancer: a systematic review and meta-analysis

Abstract: CEIs/ARBs therapy might be associated with a reduce risk of CRC development, but whether use of these medications improves the outcomes of CRC remains unknown. Large-scale and more robust studies are needed to further explore this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…In addition, a recently published meta-analysis of observational studies [10] also found a protective effect of the combination of ACEis or ARBs against CRC. Regarding overall ACEis effect, we found a similar protection to that found in other studies combining ACEis and ARBs in their analyses [9,10], but our results found only borderline significance. It is remarkable that this protection increased substantially in the under 65-year age group and less markedly in men.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, a recently published meta-analysis of observational studies [10] also found a protective effect of the combination of ACEis or ARBs against CRC. Regarding overall ACEis effect, we found a similar protection to that found in other studies combining ACEis and ARBs in their analyses [9,10], but our results found only borderline significance. It is remarkable that this protection increased substantially in the under 65-year age group and less markedly in men.…”
Section: Discussionmentioning
confidence: 96%
“…Nowadays, the role of aspirin therapy in the reduction of colorectal cancer risk and precancerous adenomas [3,4] is well known and there is increasing evidence of the chemopreventive effect of many others drugs used for cardiovascular diseases such as statins [5] and renin-angiotensin system (RAS) inhibitors [6]. In addition, recent observational studies and one meta-analysis have shown a protective effect of RAS therapy against CRC [7][8][9][10]. Despite these encouraging findings, other studies have yielded conflicting results [11][12][13], calling for additional studies before recommending the clinical use of RAS inhibitors for CRC chemoprevention.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 11 observational studies examining 113,048 individuals found a 6% decreased incidence of colon cancer in individuals on ACE inhibitors or angiotensin receptor blockers (ARBs). 109 Most other work has examined whether the use of ACE inhibitors, ARBs and β-blockers affect cancer outcomes. 110112 In the Life After Cancer Epidemiology (LACE) cohort of breast cancer survivors, risk of breast cancer recurrence was slightly increased in women on ACE inhibitors (HR 1.56; 95% CI, 1.02–2.39) and decreased in those on β-blockers (HR 0.86; 95% CI, 0.57–1.32).…”
Section: Cardiac Risk Factors and Cancer Outcomesmentioning
confidence: 99%
“…For example, whilst beta-adrenergic blockers could provide benefit against some breast cancers (e.g. triple-negative), long-term use of calcium channel inhibitors may be risky [23,24]. This may not be surprising, however, since cancer is a complex disease and drug effects especially must be evaluated on specific cancers, subtypes and stages.…”
Section: Clinical and Lifestyle Implicationsmentioning
confidence: 99%